Can introvoxel incoherent motion MRI be used to differentiate patients with placenta accreta spectrum disorders? - Tao Lu; Hong Pu; Kui-de Li; Jie Mei; Meng-wei Huang; Shao-yu Wang (BMC, 2019)
Abstract Background The incidence of PAS disorders increased rapidly in recent years, and introvoxel incoherent motion (IVIM) MRI has been applied in the assessment of placenta. The study aims to investigate whether the parameters from IVIM can be used to differentiate patients with PAS disorders complicating placenta previa and secondly to differentiate different categories of PAS disorders. Methods The study participants were comprised of 99 patients with placenta previa, including 16 patients with placenta accreta, 51 patients with increta, 8 patients with percreta and 24 patients without PAS disorders between 28 + 0 and 39 + 6 weeks. IVIM MRI was performed on a 1.5 T scanner. Perfusion fraction (f), pseudodiffusion coefficient (D*) and diffusion coefficient (D) were calculated. Results Women with PAS disorders had a higher perfusion fraction (p = 0.019) than women without the disease. Multiple comparisons showed perfusion fraction in patients without PAS disorders was significantly lower than in patients with placenta accreta and percreta(P = 0.018 and 0.033 respectively), but was not lower than in patients with increta(p = 1). Conclusion Patients with placenta accreta and percreta differed in placental perfusion fraction from women with increta and without PAS disorders.